SSRI-Human Entanglements: On Becoming with Antidepressants - Javier García-Martínez (Archivio Antropologico Mediterraneo, 2025)
Biomedical research considers antidepressants in terms of “effectiveness” and “adverse events,” but an ethnographic approach can reveal the intersections between Selective Serotonin Reuptake Inhibitor (SSRI) antidepressants and humans through an analysis of lived experiences. I analyse lived experiences and the transformative effect of SSRI treatment on daily practices through digital ethnographies on the Discord platform within online mental health support communities. I propose to consider the SSRI-human intersection as multiple ontological becomings, shaped by daily practices – from taking the pill to experiencing both adverse and desired bodily changes. These transformations range from emotional numbness, loss of libido, a conflicted sense of self, or increased productivity. These intersections also transform the ontology of antidepressants understood as “pharmakon,” altering their perception as either “good” or “bad,” medicine or poison.